Prevalence of electronic cigarette use and its respiratory complications among medical students at a private university in Teresina-PI (Research, Society and Development, 2023)
Electronic cigarettes (e-cigarettes) are battery-operated devices that allow users to vaporize (the act of inflating an electronic cigarette) aerosols containing nicotine and flavors. The objective of the study is to analyze the prevalence of EC use among medical students, as well as to list and relate the presence of respiratory symptoms with the use of EC. The study was carried out with a sample of 316 medical students aged between 18 and 35 years old, who use or do not use electronic cigarettes. Exclusion criteria will be students who provided inaccurate information and incompletely answered the questionnaire. Currently, most young people are aware of the existence of electronic cigarettes. This is due to the greater dissemination by companies producing ECs of aggressive advertisements to encourage their use. EC consumption has been associated with increased peripheral airway resistance and the fraction of exhaled nitric oxide, with characteristics similar to the effects of tobacco smoke, and lung injury associated with the use of EC products. It is fundamental to have interventions that aim to encourage healthy habits among students and inhibit the adoption of the use of this type of device, ultimately avoiding the increase in the consumption of other products that also release inhaled nicotine, including tobacco derivatives. More research is needed focusing on its consequences, e-liquid constituents, user characteristics and usage patterns.